Synthesis and characterization of layered alkaline manganates, titanates, and molybdates for supercapacitor applications - Radhiyah, Abd Aziz (2016)
Development of pseudocapacitors, in which electrical charge is stored through a redox reaction when it is brought in contact with an electrolyte, is an active area of research to achieve high energy density (ES) and power density (PS) in supercapacitors. Many promising materials such as RuO2, -MnO2, Co3O4 are proposed as desirable pseudocapacitor electrodes; however, they are either poorly abundant and toxic or resistive and difficult to be synthesized. On the other hand, there are several highly abundant transition metal oxides exhibiting poor and/or non-capacitive behavior such as titanium dioxide (TiO2) and some polymorphs of manganese oxide (-MnO2). It is hypothesized that making a layered structure of the above metal oxides could enhance their electrochemical performance because the lamellar space between the layers could easily intercalate/de-intercalate of ions. Consequently, this thesis aims to synthesize layered analogues of TiO2, -MnO2 by incorporating hydrated alkaline ions and study their electrochemical properties. Effect of incorporating hydrated alkaline ions in an intrinsically layered material, i.e., Mo9Se11, on its electrochemical properties has also been undertaken to make a contrast. The physicochemical characterization was analyzed using X-ray diffraction (XRD), selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscope (FESEM), transmission electron microscope (HRTEM) and Brunauer-Emmett-Teller (BET) surface analyzer. The electrochemical properties of the samples were studied by cyclic voltammetry (CV), galvanostatic charge-discharge cycling (GCD) and electrochemical impedance spectroscopy (EIS) in a three-electrode system configuration. A comprehensive investigation on the structure and properties of the materials before and after incorporation has been undertaken and the results are discussed deeply. It showed that alkaline layered structure of manganate and titanate material exhibits ~2.5 and ~16 times higher specific capacitance (CS) than that of the non-layered ones in optimized electrolytes. However, alkaline layered molybdate material shows 6 times lower CS value than non-alkaline layered structure. The capacitive performance was correlated with the characteristic resistance and time of the electrodes employing EIS. The energy storage capability of the layered structure materials is evaluated by assembling asymmetric supercapacitors (ASC) using the layered materials as anode and commercial activated carbon as cathode. The electrochemical performance of ASCs were compared with the symmetric device fabricated using the commercial activated carbon (AC). The best performing ASCs delivered ES of ~63, ~17, and ~42 Wh/kg at PS of ~962, ~600, and ~960 W/kg for Na-MnO2//AC, Na2Ti2O4(OH)2//AC, and Mo9Se11//AC cells in the optimized electrolytes of 1M LiOH, 1M KOH and 3M LiOH, respectively, which are an order of magnitude higher than that achieved by the AC//AC device. Among them, Na-MnO2//AC showed ~98% retention of charge storage, which is much superior to the other devices; therefore, this device is promising to further develop for commercial applications.